Tecniche elettriche ed elettro-magnetiche per la caratterizzazione del permafrost: casi nelle Alpi orientali - Sirch, Fabio (2022)
The aim of this essay is to illustrate the use of electrical and electromagnetic geophysical methods for glaciological purposes; electrical resistivity tomography (ERT) and electromagnetic method in frequency domain (FDEM) have been used to characterize the active layer of permafrost on three different rock glaciers sites in the Eastern Alps. Measures were carried out on the rock glaciers sites of Hintergrat and Murfreit, both in Alto Adige, belonging to the Ortles-Cevedale Group and the Sella Group, and on the Piz Boé rock glacier, which is also located on the Sella Group (Veneto side). The geoelectric data collected in the field have been first processed and then reversed through the ProfileR software. The use of the graphical interpolation program Surfer has finally made possible the creation of images representing sections of resistivity to which apply a geological interpretation. Data obtained from electro-magnetic measurements were not reversed, filtering the signal was enough to remove the values without any physical significance and, successively, interpret the images related to sections of apparent conductivity, once again obtained with the Surfer software. Moreover, the images obtained by the two methods have been compared each other with the aim of identifying common points and assessing if the two techniques can actually provide similar results. What emerged at the end of this study is the fact that the two geophysical methods, although presenting a different resolution, were sufficiently comparable. Geoelectric measurements show the advantage of better resolution and depth of investigation but their logistics limitation makes it difficult to perform numerous measurements in a short time. The FDEM method, on the other hand, allows to acquire many lines in a short time, while maintaining the disadvantage of the lower depth of investigation and the lower resolution, but the latter is still sufficient to identify the active layer of permafrost or identify points of particular interest on which further ...